Prevalence and Subtype Analysis of Blastocystis hominis Isolated from Patients in the Northeast of Iran. (15th January 2021) - Salehi, Mitra; Mardaneh, Jalal; Niazkar, Hamid Reza; Minooeianhaghighi, Mohammadhaasan; Arshad, Elahe; Soleimani, Fateme; Mohammadzadeh, Alireza
Abstract : Blastocystis hominis is the most common intestinal parasite found in humans and many other hosts. Pathogenicity of Blastocystis spp. remains controversial, and it has been suggested that it may be associated with specific subtypes of the organism. This study identified the B. hominis subtypes and their prevalence rates in the northeast of Iran. A total of 1878 samples were collected from the northeast of Iran from January to December 2017. The patients' demographic details were recorded. Samples were examined by a wet mount, and genomic DNA was extracted from positive samples. Also, PCR was done on the positive samples, and sequencing and phylogenetic analysis were subsequently performed. From 1878 collected stool samples, 152 (8.1%) Blastocystis samples were detected by the microscopic method. Of the 152 samples, Blastocystis spp. were found in 53.6% of the men and 28.9% of the women who showed clinical gastrointestinal symptoms, and a significant relationship was observed between gender and clinical symptoms (P = 0.002 ). A meaningful relationship was found between the season and infection with this parasite (P value = 0.003). The results of the sequencing of 22 PCR products showed the dominance of ST3, which was isolated from 10 (45.45%) patients, while ST1, ST2, and ST7 were found in 4 (18.19%), 7 (31.81%), and 1 (4.55%) patients, respectively. In this study, ST7 had a low prevalence in the northeast of Iran, and similar to previous studies, ST3 was the dominant subtype.